(3bGfhf GdELQGAGJ GdeOfjI (B:s (3efaM HGdJYOjdGJ GdLOjOI (B/s - (3Hf HdbGSe,Ydj s ((3HGJfI (B:s (3GdOGQ GdeZGQHjI GdOhdjI (B;(3eWHYI YeGQ bQaj ,s, 1991)
(3gPG GdcJGH GdLOjO GdPj JVYg GdOGQ GdeZGQHjI GdOhdjI Hjf CjOj GdgJejf HGdeSGFd GdbGfhfjI GdELQGFjI jYJHQ QcjRI CSGSjI aj eeGQSI GdbVGA GdeOfj aGdELQGAGJ GGdeOfjI gj GdeMQc GdPj HhGSWJg jJe JWHjb CMcGe GdbGfhf GdeOfj aj GdeLGd GdYdej Gdjhej eeG jSGYO GdeLJeY Ydi aV fRGYGJg GdYOjOI h GdeJfhYI GdCTcGd HGdWQb GdSdejI GdJj JJUa HgG cd JNVY ddefWb GdbGfhfj (B.(3hbO jajO gPG GdcJGH GdeMGej h GdbGVj h GdehKb hGdefaP GdTQYj hcPG WdHI eYGgO GdMbhb h GdEOGQI ceG jge eSjQj GdEOGQGJ GdYehejI h GdeDSSGJ GdEbJUGOjI dGSjeG eUGdM GdefGRYGJ (B.s
Keywords: (3GdELQGAGJ s; (3GdeOfjI s; (3bGfhf s